2003
DOI: 10.1021/bi0345844
|View full text |Cite
|
Sign up to set email alerts
|

Two Redox-Active β-Carotene Molecules in Photosystem II

Abstract: Photosystem II (PS II) contains secondary electron-transfer paths involving cytochrome b(559) (Cyt b(559)), chlorophyll (Chl), and beta-carotene (Car) that are active under conditions when oxygen evolution is blocked such as in inhibited samples or at low temperature. Intermediates of the secondary electron-transfer pathways of PS II core complexes from Synechocystis PCC 6803 and Synechococcus sp. and spinach PS II membranes have been investigated using low temperature near-IR spectroscopy and electron paramag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 33 publications
(69 reference statements)
2
83
0
Order By: Relevance
“…observed in spinach and WT Synechococcus and Synechocystis PS II samples have been observed in the range of 980 -1000 nm (11). The terminal double bonds of ␤-carotene are located within the ␤-ionylidene rings, which are forced out of the plane of conjugation with the rest of the polyene chain because of steric repulsion between the methyl groups on the ring and the polyene chain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…observed in spinach and WT Synechococcus and Synechocystis PS II samples have been observed in the range of 980 -1000 nm (11). The terminal double bonds of ␤-carotene are located within the ␤-ionylidene rings, which are forced out of the plane of conjugation with the rest of the polyene chain because of steric repulsion between the methyl groups on the ring and the polyene chain.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature Dependence of Carotenoid Oxidation-Tracewell and Brudvig (11) showed that the Car ϩ band in WT Synechocystis can be fit by two Gaussians, one centered at 982 nm (Car A ϩ ) and another at 1027 nm (Car B ϩ ). Although both Car A ϩ and Car B ϩ are ␤-carotenes, the difference in the absorbance maxima was attributed to differences in the local environments of the two carotenoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each oxidation state generated in the oxygen-evolving centre (OEC) is represented as an intermediate of the S-state cycle ( Joliot et al 1969;Kok et al 1970) of which there are five distinct states (S0-S4). In addition to these reactions, side reactions can occur under some conditions including the oxidation of a high-potential cytochrome bound within the PSII core complex (Cyt b559), a b-carotene molecule and a Chl a molecule (Chl Z ; Stewart & Brudvig 1998;Faller et al 2001;Telfer 2002;Tracewell & Brudvig 2003). These side reactions occur on the tens of millisecond time scale and therefore do not compete with the electron transfer pathway leading to water oxidation.…”
Section: The Reactions Of Psiimentioning
confidence: 99%